RPA-CRISPR-Cas13a-assisted detection method of transmissible gastroenteritis virus - Wang, Haoyu; Cheng, Zhimeng; Luo, Ran; Yang, Qiyue; Zeng, Yongping; Yang, Yijun; Chen, Yuankun; Li, Wenting; Liu, Xiao (Frontiers in Veterinary Science, 2024)
Background and aim: Transmissible gastroenteritis virus (TGEV) is a highly contagious gastrointestinal virus that causes diarrhea, vomiting, anorexia, dehydration, and weight loss in piglets. In clinical practice, it often occurs in mixed infections with other pathogens, and is therefore difficult to diagnose and prevent. It mainly harms piglets of about 2 weeks old, causing huge losses on farms. The clinical confirmation of TGEV usually requires a laboratory diagnosis, but traditional PCR and immunofluorescence assays have some limitations. Moreover, most farms in China are ill-equipped to accurately diagnose the disease. Therefore, a new detection method with high sensitivity and specificity and less dependence on instrumentation is required.We used recombinase polymerase amplification (RPA), combined with the nuclease characteristics of the activated Cas13a protein to establish a visual CRISPR-Cas13a-assisted detection method for TGEV by adding a reporter RNA with fluorescent and quenching moieties to the system. result: We selected the optimal RPA primer and best CRISPR RNA (crRNA). The reaction system was optimized and its repeatability, specificity, and sensitivity verified. The TGEV detection system did not cross-react with other common diarrhea viruses, and its detection limit was 10 1 copies, which is similar with the sensitivity of qPCR. We successfully established an RPA-CRISPR-Cas13a-assisted detection method, and used this detection system to analyze 123 pig blood samples. qPCR was used as the gold standard method. The sensitivity, specificity, positive coincidence rate, and negative coincidence rate of the new method were 100%, 98.93%, 96.66%, and 100%, respectively.